1992
DOI: 10.1177/002383099200500107
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Antidepressants in the Elderly: 1986 and 1989

Abstract: Depression is a frequent disorder in the elderly that is often treated with antidepressants. It is generally accepted that, since all antidepressants are equally effective and the elderly are differentially more susceptible to side effects, those antidepressants with the least side effects should be preferentially used. The actual use of antidepressants in 1986 and 1989 was reviewed. We found that (1) contrary to expectation, antidepressants were prescribed in 1986 in quantities that were directly proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The older antidepressants, particularly amitriptyline, caused the most side-effects, confirming previous strong recommendations that these be avoided (Gerson et al, 1988;Dewan et al, 1992). Given its marked side-effect profile, amitriptyline, when used as a comparator, may have exaggerated the beneficial side-effect profile of newer drugs.…”
Section: Tertiary Aminessupporting
confidence: 68%
“…The older antidepressants, particularly amitriptyline, caused the most side-effects, confirming previous strong recommendations that these be avoided (Gerson et al, 1988;Dewan et al, 1992). Given its marked side-effect profile, amitriptyline, when used as a comparator, may have exaggerated the beneficial side-effect profile of newer drugs.…”
Section: Tertiary Aminessupporting
confidence: 68%
“…One might suppose that doctors might have prescribed tricyclics with caution and that the advent of 'safer' serotonin reuptake inhibitors might have changed prescribing habits. However, Dewan et al (1992) found that in comparing the use of antidepressants in the elderly in 1986 and 1989, in 1986 antidepressants were prescribed in quantities that were directly proportional to their side-effects, ie the greater the side-effects, the more they were used.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, specific psychotherapies can be examined, such as cognitive behavioral therapy (CBT), but more attention should also be given to effects of the most common kind of psychotherapy, a nonspecific eclectic mix of mostly psychoanalytic techniques with supportive and behavioral methods, which is highly understudied (66). A final kind of psychotherapy that is little studied and may have particular benefit in depressive conditions is existential psychotherapy (67), which, despite its apparently subjective nature, is amenable to empirical assessment of outcomes (68).…”
Section: Suggestions For Future Researchmentioning
confidence: 99%